2002
DOI: 10.1080/08916930290013441
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Molecules and Autoimmune Thyroid Diseases

Abstract: At least two signals for proliferation and cytokine secretion by T-cells are required. The first signal is delivered through the interaction of the T-cell receptor with major histocompatibility complex (MHC) molecules expressed on the surface of antigen-presenting cells (APC). The second or costimulatory signal is delivered by cell surface molecules expressed by APC. The interaction of B7.1/B7.2 with CD28 provide the most potent costimulatory signal for T-cell activation. CD40 antigen and its ligand (CD40L) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 72 publications
2
29
0
Order By: Relevance
“…Furthermore, CTLA-4 has a role in induction of Th1 response and suppression of Th2 cytokines, an effect that is antagonized by CD28. The balance between CD28 and CTLA-4 expression by T lymphocytes could be a factor in the pathogenesis of autoimmune diseases [28]. In our study, we found an increased percentage of lymphocytes expressing costimulatory molecules with higher detection of the CD28 population on resting and active cells, which is associated with growing dominance of Th2 immune response in the peripheral blood in untreated patients with GD.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, CTLA-4 has a role in induction of Th1 response and suppression of Th2 cytokines, an effect that is antagonized by CD28. The balance between CD28 and CTLA-4 expression by T lymphocytes could be a factor in the pathogenesis of autoimmune diseases [28]. In our study, we found an increased percentage of lymphocytes expressing costimulatory molecules with higher detection of the CD28 population on resting and active cells, which is associated with growing dominance of Th2 immune response in the peripheral blood in untreated patients with GD.…”
Section: Discussionsupporting
confidence: 54%
“…This notion led us to the hypothesis that the blockade of CD29 activation could therefore be a therapeutic target for the suppression of relevant diseases (Salmaso et al 2002). By this logic, we established quantitative screening models to develop novel CD29 functional regulators, using specific agonistic antibodies to CD29, other CD29-associated adhesion molecules, such as CD147 and CD98 (Cai et al 2005;Cho et al 2001;Tsurudome and Ito 2000), and matrix protein fibronectin (FN) to functionally activate CD29 in U937 cells (Cho 2008;Cho et al 2001Cho et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In their hypothesis, thyroid cells in autoimmune thyroid diseases aberrantly express MHC class II antigen and, as non-professional antigen-presenting cells, present thyroid-specific autoantigens to naïve T cells, leading to thyroid autoimmune reaction. However, the lack of expression of costimulatory molecules B7 on thyrocytes [27] suggests induction of tolerance rather than immunity [28]. More recently, thyroid-specific MHC class II transgenic mice did not spontaneously develop autoimmune thyroid disease [29,30].…”
Section: Implications Of Animal Models In Disease Pathogenesismentioning
confidence: 99%